(untitled) (Economia Aplicada, 2019)
This paper aimed to analyze the price transmission and marketing margins among the segments of beef production chain (farm, wholesale and retail), looking for evidence of possible exercise of market power. Two Vector Error Correction models were estimated based on Houck’s framework. The results indicate symmetry in price transmission between wholesale and retail and price asymmetry between wholesale and producer. Thus, there is some evidence of the possible exercise of market power only from downstream to upstream (from wholesale to producer). This may be explained by differences in market structure, as retail and wholesale are oligopolies, unlike producers.